UV-light modulated Ti3C2Tx MXene/g-C3N4 heterojunction film for electromagnetic interference shielding - Zhou, Qianfan; Qian, Kunpeng; Fang, Jianhui; Miao, Miao; Cao, Shaomei; Feng, Xin (Composites. Part A, Applied science and manufacturing, 2020)
•Ti3C2Tx/g-C3N4 heterojunction films were assembled via a pressured-extrusion.•The heterojunction films have high conductivity and good mechanical flexibility.•The heterojunction films exhibit EMI SE of 42.99 dB with thickness of 28.2 µm.•UV-light is assistance to modulate conductivity and EMI shielding performance. With the mushrooming of smart electronic devices, ultrathin Ti3C2Tx MXene based EMI shielding materials with long term durability have aroused much interest. Herein, 2D Ti3C2Tx/g-C3N4 heterojunction films were firstly assembled using cellulose nanofibrils (CNF) as green binder via a solution-based pressured-filtration process. The heterojunction film with Ti3C2Tx/g-C3N4 mass ratio of 5:1 (28.20 µm in thick) exhibited distinguished performance with EMI shielding effectiveness of 42.99 dB in X-band and high tensile strength of 23.85 MPa. Specially, the generation of photo-electrons from g-C3N4 nanosheets reduced TiO2 into lower valence states under 365 nm UV light-irritation, resulting in lower loss on electrical conductivity as well as EMI shielding performance compared to their unilluminated counterparts. The reduction on TiO2 offered by the g-C3N4 enables the heterojunction film to be considered as a promising alternative EMI shielding material for future potential applications, because it can run long time just need UV light modulation.